Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3382/ps/pew310
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of white striping and wooden breast in broilers fed grower and finisher diets with increasing lysine levels

Abstract: Two experiments were conducted to evaluate the prevalence and severity of white striping (WS) and wooden breast (WB) in breast fillets from broilers fed diets with increasing digestible Lysine (dLys) from 12 to 28 d (Exp. 1) and from 28 to 42 d (Exp. 2). Trials were sequentially conducted using one-d-old male, slow-feathering Cobb 500 × Cobb broilers, both with 6 treatments and 8 replicates. Increasing dLys levels were equally spaced from 0.77 to 1.17% in Exp. 1 and from 0.68 to 1.07% in Exp. 2. The lowest dLy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
54
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 37 publications
11
54
0
4
Order By: Relevance
“…Several studies have been conducted to ascertain the possible factors involved in the occurrence of WS, WB, and SM in fast-growing broilers (Table 4). It is widely accepted that the incidence of breast abnormalities rises with increasing slaughter weight (Cruz et al, 2016;Lorenzi et al, 2014;Papah et al, 2017), growth rate (Kuttappan et al, 2012a(Kuttappan et al, , 2013a(Kuttappan et al, , 2017Lorenzi et al, 2014), and genetic potential for breast meat yield (Alnahhas et al, 2016;Bailey et al, 2015;Livingston et al, 2018;Lorenzi et al, 2014;Petracci et al, 2013;Trocino et al, 2015) in agreement with strong genetic correlations found by Alnahhas et al (2016). This has been also confirmed by histological observations which evidenced that myodegeneration progress associated with the development of breast abnormalities is strictly related to age at slaughter (Griffin et al, 2018;Kawasaki et al, 2018;Papah et al, 2017;Radaelli et al, 2017;Sihvo et al, 2017) and breast growth pattern (Papah et al, 2017) (Table 5; Radaelli et al, 2017).…”
Section: Means Of Alleviation: Facts and Challengessupporting
confidence: 58%
See 2 more Smart Citations
“…Several studies have been conducted to ascertain the possible factors involved in the occurrence of WS, WB, and SM in fast-growing broilers (Table 4). It is widely accepted that the incidence of breast abnormalities rises with increasing slaughter weight (Cruz et al, 2016;Lorenzi et al, 2014;Papah et al, 2017), growth rate (Kuttappan et al, 2012a(Kuttappan et al, , 2013a(Kuttappan et al, , 2017Lorenzi et al, 2014), and genetic potential for breast meat yield (Alnahhas et al, 2016;Bailey et al, 2015;Livingston et al, 2018;Lorenzi et al, 2014;Petracci et al, 2013;Trocino et al, 2015) in agreement with strong genetic correlations found by Alnahhas et al (2016). This has been also confirmed by histological observations which evidenced that myodegeneration progress associated with the development of breast abnormalities is strictly related to age at slaughter (Griffin et al, 2018;Kawasaki et al, 2018;Papah et al, 2017;Radaelli et al, 2017;Sihvo et al, 2017) and breast growth pattern (Papah et al, 2017) (Table 5; Radaelli et al, 2017).…”
Section: Means Of Alleviation: Facts and Challengessupporting
confidence: 58%
“…Several studies have been conducted to ascertain the possible factors involved in the occurrence of WS, WB, and SM in fast‐growing broilers (Table ). It is widely accepted that the incidence of breast abnormalities rises with increasing slaughter weight (Cruz et al., ; Lorenzi et al., ; Papah et al., ), growth rate (Kuttappan et al., , , ; Lorenzi et al., ), and genetic potential for breast meat yield (Alnahhas et al., ; Bailey et al., ; Livingston et al., ; Lorenzi et al., ; Petracci et al., ; Trocino et al., ) in agreement with strong genetic correlations found by Alnahhas et al. ().…”
Section: Means Of Alleviation: Facts and Challengesmentioning
confidence: 52%
See 1 more Smart Citation
“…This myopathy has been associated with an increased muscle hypertrophy of fast-growing chickens, witch brings about a reduced capillary supply that could result in a decreased source of nutrients and oxygen and slower removal lactic acid from breast muscles, which ultimately may lead to muscle damage [2,45].…”
Section: Histological Resultsmentioning
confidence: 99%
“…The high productive of poultry as a result of a constant increase in the world demand for white meat with a intensive genetic selection for fast growth rate and high breast yield, have been spurring the broiler industry towards practices that increase its production [1][2][3], and these factors may induce metabolic stresses that can negatively impact meat quality [4][5][6]. More recently, high growth rate and high breast yield have been associated with the occurrence of other myopathies affecting pectoralis major and other muscles, i.e., white striping [7,8].…”
Section: Introductionmentioning
confidence: 99%